EL CAMPO LABORAL DE LA ANTROPOLOGÍA en México - GUADALUPE ESCAMILLA; FERNANDO I. SALMERÓN; LAURA R. VALLADARES (Revista Colombiana de Antropología, 2007)
ANTHROPOLOGY IN MEXICO HAS A LONGSTANDING TRAJECTORY OF PROFESSIONAL INVOLVEMENT, BOTH IN academia and public settings. In this essay we stress the work of those professionals of the discipline who work outside academic settings. We undertake the discussion starting from different perspectives expressed by Mexican anthropologists who have advanced contrasting views of anthropological work. We present information about current professional settings where anthropologists are employed in Mexico, stressing the growing diversity of these niches and the challenges that young anthropologists face.